Morphology and initial development of Hancornia speciosa var speciosa in different substrates - Silva, Ana Veruska Cruz; Muniz, Evandro Neves; Souza, Juliana Lopes; Soares, Adrielle Naiana Ribeiro; Ledo, Ana da Silva (Comunicata Scientiae, 2025)
The impact of commercial demand on fruits explored through extractivism requires sustainable production strategies. Among these strategies is seedling propagation for reforestation and/or commercial plantations. The substrate and its impact on the quantity and quality of propagated plants are critical aspects of seedling propagation. Hancornia speciosa, commonly known as mangabeira, is a native fruit species that has been primarily explored through extractivism; thus, the goal of this study was to assess the early development of H. speciosa var. speciosa seedlings in different substrates using morphophysiological parameters. The seeds were processed and sown in six different substrates (sand, sand + powder coconut coir, sand + vermiculite, commercial substrate, commercial substrate + powder coconut coir, vermiculite, commercial substrate + vermiculite). To evaluate seedling development, the parameters First Emergence Count, Emergence Percentage, Emergence Speed Index, Total Seedling Size, Shoot Height, Root Length, Stem Diameter, Number of Leaves, and Shoot and Root Dry Massa were used. The pure vermiculite substrate performed best across all parameters, followed by the commercial substrate + powder coconut coir and the commercial substrate. As a result, substrates containing pure vermiculite are recommended for the propagation of H. speciosa var. speciosa, whereas substrates containing higher concentrations of sand, 50 to 100%, have a negative impact on seedling development for this variety.